Effect of heme oxygenase-1 on ochratoxin A-induced nephrotoxicity in mice. (March 2017) - Loboda, Agnieszka; Stachurska, Anna; Podkalicka, Paulina; Sobczak, Mateusz; Mucha, Olga; Witalisz-Siepracka, Agnieszka; Jozkowicz, Alicja; Dulak, Jozef
Graphical abstract: Abstract: Heme oxygenase-1 (HO-1), a heme-degrading enzyme, is suggested to play an important role in kidney pathophysiology, mostly due to its anti-fibrotic, anti-apoptotic and anti-oxidant properties. One of the mycotoxin, ochratoxin A (OTA) was previously shown to affect HO-1 expression, however, the mechanisms of OTA-induced nephrotoxicity during HO-1 deficiency are unknown. We have shown that OTA regulates the number of pro-fibrotic, pro-inflammatory, anti-oxidative and pro-apoptotic factors in HO-1 dependent manner, as the lack of HO-1 accelerates whereas the induction of HO-1 expression by cobalt protoporphyrin (CoPP) attenuates nephrotoxic effect of OTA. The down-regulation of the nuclear factor-erythroid-2- related factor 2 (Nrf2) transcription factor by OTA, observed in HO-1 knock-out animals, might be another mechanism of OTA toxicity. Moreover, HO-1 level and OTA treatment influences the expression of microRNAs. Namely, p53-regulated miR-34a and pro-fibrotic miR-21 were already increased in HO-1 −/− kidneys and were further induced by OTA administration, whereas anti-fibrotic miR-29c was down-regulated by this mycotoxin. Our study indicates that complex mechanisms of OTA nephrotoxicity may be partially overcome by HO-1 induction.